ANALISIS PERSEPSI KESULITAN MATERI PERKULIAHAN FISIKA PADA MAHASISWA VOKASI BERLATAR SEKOLAH MENENGAH KEJURUAN - Kurnia, Ahmad (Jurnal TEDC, 2026)
The transition from Vocational High School (SMK) to higher technical education often presents significant academic hurdles, particularly in Physics. This gap is largely attributed to the SMK curriculum, which typically limits Physics instruction to only two semesters. To address this, a descriptive quantitative study was conducted at TEDC Polytechnic Bandung to map the perceptions of Electrical Engineering students across various Physics topics. Using a Likert scale survey, the research revealed a stark contrast between General and Electrical Physics. Modern Physics was identified as the most challenging topic by 59% of students due to its abstract nature. Conversely, 86% of respondents labeled Direct Current (DC) as the easiest. However, this high confidence level raises concerns regarding the “Illusion of Competence”, where students feel they have mastered the subject by simply performing mathematical procedures without grasping the fundamental concepts. Statistical data showed a difficulty score of 3.18 for General Physics and 2.79 for Electrical Physics. While students perceive a strong foundation in electricity, the study emphasizes a necessary pedagogical shift. The primary recommendation is to move away from procedural-mathematical methods toward phenomenon-based contextual learning. This approach ensures students do not merely memorize formulas but instead construct a profound, conceptual understanding of science.